Simultaneous O2 plasma and thermal treatment for improved surface conductivity of Cu-Doped SnO2 films - Somjaijaroen, Natthawirot; Sakdanuphab, Rachsak; Chanlek, Narong; Chirawatkul, Prae; Sakulkalavek, Aparporn (My University, 2019)
Cu-doped SnO2 thin films were deposited on a glass substrate using radio frequency magnetron sputtering. The effects of varying the O2 partial pressure during the deposition process and post-O2 plasma treatment at 420 °C were investigated. Bulk and surface oxidation states were measured by X-ray absorption near-edge structure spectroscopy and X-ray photoelectron spectroscopy. The as-deposited films exhibited oxygen deficient compositions and Cu+ or Cu2+ ions, which depend on the deposited O2 partial pressure. After the post-plasma treatment, the films changed from an amorphous structure into a low crystalline film. X-ray diffraction results indicated substitutional doping, wherein some Sn4+ ions were replaced with Cu+ or Cu2+ ions. The O2 plasma treatment can remove Cu2+ and O2− from the film surface. The oxygen deficiency defects and Cu+- or Cu2+- doped present at the surface are the key factors in controlling the sheet resistance of the Cu-doped SnO2 film. The minimum sheet resistance was obtained after the plasma treatment of the films deposited at a 2% O2 partial pressure.
Keywords: Copper-doped tin dioxide; Oxygen deficiency; Oxygen plasma treatment; Sputtering; Tin dioxide